2021
DOI: 10.3390/cancers13246186
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated MR Based Virtual Biopsy of Cerebral Gliomas

Abstract: Objective: The aim of this study was to investigate the diagnostic accuracy of a radiomics analysis based on a fully automated segmentation and a simplified and robust MR imaging protocol to provide a comprehensive analysis of the genetic profile and grading of cerebral gliomas for everyday clinical use. Methods: MRI examinations of 217 therapy-naïve patients with cerebral gliomas, each comprising a non-contrast T1-weighted, FLAIR and contrast-enhanced T1-weighted sequence, were included in the study. In addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…reported that the predictive accuracy of MGMT status was 0.67, while Johannes Haubold et al . reported that the AUCs of predicting MGMT status were 0.854 and 0.742 in validation and test sets, respectively [ 27 , 28 ]. In addition, Yibin Xi et al .…”
Section: Discussionmentioning
confidence: 99%
“…reported that the predictive accuracy of MGMT status was 0.67, while Johannes Haubold et al . reported that the AUCs of predicting MGMT status were 0.854 and 0.742 in validation and test sets, respectively [ 27 , 28 ]. In addition, Yibin Xi et al .…”
Section: Discussionmentioning
confidence: 99%
“…The system provided an AUC (validation/test) of 0.981 ± 0.015/0.885 ± 0.02 for the grading task. The prediction of the ATRX (−) condition had the best results, with an AUC of 0.979 ± 0.028/0.923 ± 0.045, followed by the prediction of IDH1/2(+), with an AUC of 0.929 ± 0.042/0.861 ± 0.023, while they showed only moderate results for the prediction of 1p19q and MGMT status [ 82 ].…”
Section: Tumor Characterizationmentioning
confidence: 99%
“…Therefore, the scientific effort has increasingly focused on improving and streamlining the imaging of meningiomas prior to therapy. A variety of publications are dedicated to novel methods in imaging of intracranial neoplasms, such as the implementation of radiomics [8][9][10] or advanced multiparametric MRI [4,11,12]. Here, especially diffusion-weighted imaging (DWI), a marker for cellular density in tissue, might be of considerable interest [13].…”
Section: Introductionmentioning
confidence: 99%